Bankruptcies in Temporary Equilibrium Forward Markets With and Without Institutional Restrictions - Stahl, Dale O. (Review of Economic Studies, 1985)
Sufficient conditions are found for the existence of an orderly sequence of temporary equilibria in economies with incomplete forward markets without exogenous limits on short-sales. In the absence of institutionally imposed trade restrictions, equilibrium exists under the assumption of overlapping expectations. In the institutional model a clearinghouse imposes rules of trade (interpreted as margin requirements) to reduce the likelihood of bankruptcies. Under this rule, equilibrium exists without overlapping expectations, and subsequent bankruptcies are less likely.